Healthcare technology innovation adoption : electronic health records and other emerging health information technology innovations /: electronic health records and other emerging health information technology innovations. (2016) - Daim, Tugrul Unsal, 1967-; Behkami, Nima A; Başoğlu, Nuri; Kök, Orhun M; Hogaboam, Liliya, 1976-
No abstract available